MORE THAN JUST HORSE: DIETARY BREADTH AND SUBSISTENCE IN BRONZE AGE CENTRAL MONGOLIA - LEE G. BRODERICK; JEAN-LUC HOULE (Mongolian Journal of Anthropology, Archaeology and Ethnology, 2023)
Our current state of knowledge of subsistence strategies and dietary breadth in Bronze Age Mongolia has been hampered by a monument focused research paradigm, which has largely ignored habitation sites. This approach has skewed our understanding by extrapolating the ordinary from the extraordinary. The Khanuy Valley Project has recently excavated Bronze Age transhumant habitation sites in central Mongolia and recovered the associated faunal remains. Analysis has revealed a complex subsistence strategy focused on the herding of several species of domestic animal, with dietary breadth increased through the minimal exploitation of wild resources.